The Effect of Pre-Marriage Counseling on Pregnancy Preparation at the Gesang Health Center - Efi Purwanti; Homsiatur Rohmatin; Farianingsih Farianingsih (Jenggala : Jurnal Riset Pengembangan dan Pelayanan Kesehatan, 2023)
Pre-marital counseling is a medical examination carried out by health workers such as midwives for prospective brides before marriage to prepare for a healthy and planned pregnancy. The purpose of this study was to determine the effect of pre-marital counseling on pregnancy preparation at the Gesang Health Center. The design of this study used cross sectional by using 35 respondents. The sampling technique used in this study is to use total sampling. The measuring tool in this study is to use a respondent's questionnaire. Spearman's rho test was used to answer the purpose of this study. The results of this study showed that 35 respondents answered Pre-Marriage counseling questions with good and very good Likert scale qualifications of 100%. It can be said that all respondents were ready to marry. Respondents who answered the question of preparation for pregnancy with the qualifications of the Likert scale were sufficient, good, and very good as much as 100%, it can be said that the respondent had prepared for pregnancy. There is a significant influence on the relationship between Pre-Marriage counseling and pregnancy preparation. This study found that there was a relationship between pre-marital counseling and pregnancy preparation, namely p-value 0.001.